Biology concepts and applications - Starr, Cecie; Starr, Lisa; Evers, Christine A. (Cengage Learning, 2015)
In this book, each chapter challenges students to question what they read and apply the concepts learned, providing students with the critical thinking skills and science knowledge they need in life.